Atos de Fala e Referenciação na (des)construção de Faces Públicas nos “bastidores” de Notícias Políticas - Marlow, Rosani Muniz (2021)
The technological evolution has transformed journalistic work, created new forms of interaction and gave visibility to misinformation phenomena; backstage is, in journalistic practice, one of the most recurrent jargons; the off source is, for the journa